Evaluasi Pelaksanaan Corporate Social Responsibility di PT Bank Rakyat Indonesia (Persero) Tbk - Ria Silviani; Rosinta Ria Panggabean (Bina Nusantara University, 2015)
The purposes of this research are to know how Corporate Social Responsibility (CSR) activity was, to know CSR activity using ISO 26000 standard, and to evaluate ISO 26000 reporting and disclosure in PT Bank Rakyat Indonesia (Persero) Tbk using GRI 4.0 standard. The object of this research was PT Bank Rakyat Indonesia (Persero) Tbk. Research used qualitative method with primary data from interview with Divisi Sekretariat Perusahaan KP BRI and annual report dan sustainability report analysis, while secondary data was literature study related with the research. BRI is a BUMN bank that has exclusive program. It is Program Kemitraan dan Bina Lingkungan (PKBL). The guidance of PKBL is Peraturan Menteri Negara BUMN No.PER-20/MBU/2012 about Program Kemitraan BUMN dengan Usaha Kecil dan Program Bina Lingkungan. At the end, the company’s vision and mission supports the CSR company’s activity. BRI has complied with the ISO 26000 standard and has reported the implementation of ISO 26000 standard in accordance with GRI 4.0. (RS)